Kerta Desa as a Customary Judicial Institution in the Settlement of Customary Conflicts Based on Bali Provincial Regulation Number: 4 of 2019 - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi (Journal of Sustainable Development Science, 2019)
Customary conflicts that occur in indigenous communities in Bali are caused by social changes in the community that have an impact on changes in behavior, lifestyle and a shift invalues and culture. Therefore, ways and efforts are needed to resolve and reconcile disputes over conflicts or customary cases that occur. The legal issue in this study is the extent of the authority of the village Kerta institution in resolving conflicts or customary cases. This research is to use normative legal research. The regulations examined in this study are BaliProvincial Regulation Number 4 of 2019 concerning Customary Villages in Bali which is related with the existence of Kerta Desa as a customary judicial institution in the resolutionof traditional conflicts. The handling of adat conflicts is carried out by Kerta Desa as a Village Peace Judge by providing customary sanctions aimed at regulating the balance or restoring the disturbed adat order in the community.